Stability and change. Stratigraphy in early medieval Sigtuna: Methods and preliminary results - Petterson, Björn (Hikuin, 1998)
The culture-layers of Sigtuna have long attracted the interest of archaeologists. Previous excavations have been small, mere peeps into the past. Because of this there has been many suggestions but no satisfactory answer to the questions of the earliest dating and functions of the town. Many of the hypothesis were made already in the 1920’s. In November 1987 a seminar was arranged where the purpose was to summarize the research conserning early medieval Sigtuna and create a foundation for continual research. Several of the hypothesis presented at this meeting were later confirmed by the results from the Sigtuna Excavation of 1988-90, for example the structure of townplan and communication within the town.